Soil microbiota as game-changers in restoration of degraded lands - Coban, Oksana; De Deyn, Gerlinde B.; van der Ploeg, Martine (Science (American Association for the Advancement of Science), 2022)
Land degradation reduces soil functioning and, consequently, the services that soil provides. Soil hydrological functions are critical to combat soil degradation and promote soil restoration. Soil microorganisms affect soil hydrology, but the role of soil microbiota in forming and sustaining soil is not well explored. Case studies indicate the potential of soil microorganisms as game-changers in restoring soil functions. We review the state of the art of microorganism use in land restoration technology, the groups of microorganisms with the greatest potential for soil restoration, knowledge of the effect of microorganisms on soil physical properties, and proposed strategies for the long-term restoration of degraded lands. We also emphasize the need to advance the emerging research field of biophysical landscape interactions to support soil-plant ecosystem restoration practices. Soils worldwide have become increasingly degraded by human activities, especially in drylands. Land degradation negatively affects soil hydrological functioning and thereby the ecosystem services that soil provides. Soil microbes may play an important part in the restoration of degraded soils, positively influencing moisture content and other physical features of soil. Coban et al . reviewed recent work on soil hydraulic properties, potential groups of microorganisms for hydrological soil restoration based on their resilience in dry soils, and future strategies for long-term restoration of degraded lands. —AMS A review suggests that soil microorganisms may be the key to the restoration of hydraulic function in soils degraded by human activities.